Religious Education and Digital Ethics Awareness Against Doxing: A Quantitative Study of University Students in Indonesia - Fadli Firdaus; Mia Syafrina (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Doxing the non-consensual public disclosure of personal information constitutes a growing threat to digital privacy among university students in Indonesia. This study examines the influence of compulsory Religious Education learning on students' digital ethics awareness in the context of doxing. A cross-sectional descriptive-correlational survey design was employed. Using purposive sampling and Slovin's formula (e = 5%), 94 participants were recruited from a population of 123 students who had completed Religious Education at Politeknik Negeri Batam, Indonesia. Data were collected via a validated 36-item Likert-scale questionnaire (Cronbach's α = 0.912 and 0.897). Analysis incorporated descriptive statistics, Kolmogorov-Smirnov normality testing, ANOVA linearity testing, Spearman rank correlation, and simple linear regression. Most students demonstrated high Religious Education internalization (98.9%) and high digital ethics awareness (95.7%). Spearman correlation indicated a very strong positive association (rₛ = 0.833, p < .001). Simple regression confirmed that Religious Education explained 71.6% of the variance in digital ethics awareness (R² = 0.716; F = 231.90; p < .001; Cohen's f² = 2.52), with a regression coefficient of b = 0.956 (95% CI [0.832, 1.081]). Religious Education serves as a substantively effective instrument of digital character formation. The theological grounding of Islamic ethical values — particularly hifzh al-'irdh (safeguarding dignity) — appears to confer moral robustness beyond that of rule-based or literacy-oriented approaches. Implications for curriculum design, institutional policy, and interdisciplinary research on digital ethics education are discussed.